In vivo and in vitro Approach to Anti-arthritic and Anti-inflammatory Effect of Crocetin by Alteration of Nuclear Factor-E2-Related Factor 2/hem Oxygenase (HO)-1 and NF-κB Expression - Li, Yi; Kakkar, Rajat; Wang, Jian (Frontiers in Pharmacology, 2018)
The aim of the current experimental investigation to scrutinize the anti-inflammatory effect of Crocetin using the lipopolysaccharide (LPS) induced mouse macrophages (RAW 264.7) in vitro and complete Freund's adjuvant-induced arthritis model and explore invivo and explore the possible mechanism of action. RAW 264.7 macrophages were used for estimation of the effect of Crocetin on the COX-2, NO production, anti-inflammatory and inflammatory mediators (IL-10). Single intraperitoneal injection of CFA was used to induce arthritis. The rats were divided into different group and received the oral administration of Crocetin at dose-dependently and indomethacin till 28 days. The paw edema and body weight estimated at regular interval. The biochemical parameters, haematological and pro-inflammatory cytokines such as TNF-R1, IL-6, and IL-1β, VEGF; HO-1/Nrf-2 expression were estimated at end of the experimental study. At end of the experimental study, the histopathological study was also performed. Crocetin inhibited the COX-2 catalyzed PGE2 and inducible nitric oxide synthase catalyzed NO production on RAW 264.7. The paw edema and body weight was significantly (P<0.001) modulated by the Crocetin in a concentration-dependent manner. Crocetin treatment showed the modulation of biochemical and hematological parameters. Crocetin showed the alteration of TNF-α, IL-6, and IL-1β in a dose-dependent manner. The protective effect of crocetin was substantiated with reduced the expression of IL-6, IL-1β, VEGF, and TNF-R1, respectively. Crocetin also increased the HO-1/Nrf-2 and decreased the NF-κB mRNA, protein expression. On the basis of the result, we can conclude that reduction of HO-1/Nrf-2 expression, as well as inflammatory mediators, may be involved in the protective effect of Crocetin.